2018
DOI: 10.1016/j.stemcr.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 Has Distinct Molecular Functions from GDNF in the Mouse Germline Niche

Abstract: SummaryBoth glial cell line-derived neurotrophic factor (GDNF) and fibroblast growth factor 2 (FGF2) are bona fide self-renewal factors for spermatogonial stem cells, whereas retinoic acid (RA) induces spermatogonial differentiation. In this study, we investigated the functional differences between FGF2 and GDNF in the germline niche by providing these factors using a drug delivery system in vivo. Although both factors expanded the GFRA1+ subset of undifferentiated spermatogonia, the FGF2-expanded subset expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…These observations raise the possibility that FGF2 plays a role distinct from GDNF in controlling the fate of SSCs/undifferentiated spermatogonia in vivo. Our most recent studies revealed expression of Fgf2 in the germ cell population, while Gdnf is expressed in Sertoli cells and peritubular myoid cells . In these studies, germ cell depletion increased the relative expression of Gdnf , while Fgf2 was relatively suppressed .…”
Section: Self‐renewal Factors For Sscs and Establishment Of Germline mentioning
confidence: 93%
See 3 more Smart Citations
“…These observations raise the possibility that FGF2 plays a role distinct from GDNF in controlling the fate of SSCs/undifferentiated spermatogonia in vivo. Our most recent studies revealed expression of Fgf2 in the germ cell population, while Gdnf is expressed in Sertoli cells and peritubular myoid cells . In these studies, germ cell depletion increased the relative expression of Gdnf , while Fgf2 was relatively suppressed .…”
Section: Self‐renewal Factors For Sscs and Establishment Of Germline mentioning
confidence: 93%
“…Our most recent studies revealed expression of Fgf2 in the germ cell population, while Gdnf is expressed in Sertoli cells and peritubular myoid cells . In these studies, germ cell depletion increased the relative expression of Gdnf , while Fgf2 was relatively suppressed . Considering that germ cell‐depleted conditions are relatively appropriate for expansion rather than differentiation of transplanted undifferentiated spermatogonia/SSCs, the Gdnf/Fgf2 ratio might affect fate determination of undifferentiated spermatogonia/SSCs (Figure ).…”
Section: Self‐renewal Factors For Sscs and Establishment Of Germline mentioning
confidence: 94%
See 2 more Smart Citations
“…Sertoli cells also play an important role in the retinoic acid (RA) signal that promotes irreversible differentiation to Kit + spermatogonia, as Sertoli cells and different stages of germ cells cooperatively express the enzymes involved in the retinoid metabolism (Endo, Freinkman, De Rooij, & Page, ; Sugimoto, Nabeshima, & Yoshida, ; Vernet et al., ). According to in vitro studies using cultured spermatogonia and in vivo studies using transient transfection and bead implantation, fibroblast growth factor (FGF) is another important regulator of SSCs (Hasegawa & Saga, ; Kanatsu‐Shinohara et al., ; Masaki et al., ; Takashima et al., ). This notion is also supported by the analyses of causal mutations for a group of human paternal‐age effect genetic disorders (e.g., Apert syndrome and achondroplasia), which has led to the concept of selfish selection of SSCs carrying gain‐of‐function mutations in the FGF receptor or downstream effector genes that occur in fathers’ seminiferous tubules (Goriely, Mcgrath, Hultman, Wilkie, & Malaspina, ; Goriely, Mcvean, Rojmyr, Ingemarsson, & Wilkie, ).…”
Section: Elements Involved In the Open Niche Regulation Of Sscsmentioning
confidence: 99%